The Impact of Social Media on Political Mobilization and Voter Behavior in Emerging Democracies - Perveez Ahmad Khan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study investigates the impact of social media on political mobilization and voter behavior in emerging democracies. In the digital age, platforms such as Facebook, Twitter (X), WhatsApp, and Instagram have redefined political communication by enabling real-time interactions, lowering the barriers to civic participation, and amplifying grassroots movements. Focusing on case studies from India, Brazil, and Kenya, the research reveals that social media has significantly increased political awareness, especially among youth, and has become a critical tool for electoral campaigning. However, the study also highlights the darker side of digital engagement misinformation, polarization, and digital exclusion which pose challenges to democratic integrity. Employing a mixed-methods approach, including surveys, interviews, and content analysis, this paper underscores the dual potential of social media as both a catalyst for democratic participation and a vector for political manipulation. The findings call for policy reforms, digital literacy initiatives, and stronger regulatory frameworks to ensure that social media serves as a constructive force in democratic consolidation.